2011
DOI: 10.1186/1476-4598-10-42
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour effects of single or combined monoclonal antibodies directed against membrane antigens expressed by human B cells leukaemia

Abstract: BackgroundThe increasing availability of different monoclonal antibodies (mAbs) opens the way to more specific biologic therapy of cancer patients. However, despite the significant success of therapy in breast and ovarian carcinomas with anti-HER2 mAbs as well as in non-Hodkin B cell lymphomas with anti-CD20 mAbs, certain B cell malignancies such as B chronic lymphocytic leukaemia (B-CLL) respond poorly to anti-CD20 mAb, due to the low surface expression of this molecule. Thus, new mAbs adapted to each types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
1
16
0
1
Order By: Relevance
“…The JOK1 5.3 cell line (JOK1 Hairy Cell Leukemia cell lines stably transduced with human CD5 cDNA) has been described previously (40). JOK1 5.3, REH acute leukemia, MOLT4, and JURKAT T cell leukemias and K562 erythroleukemia cell lines were grown in RPMI 1640 medium supplemented with 2 mM glutamine, 10% FBS (all from Euroclone, Milano, Italy) and 110 mM gentamicin (PHT Pharma, Milan, Italy).…”
Section: Cells and Virusmentioning
confidence: 99%
“…The JOK1 5.3 cell line (JOK1 Hairy Cell Leukemia cell lines stably transduced with human CD5 cDNA) has been described previously (40). JOK1 5.3, REH acute leukemia, MOLT4, and JURKAT T cell leukemias and K562 erythroleukemia cell lines were grown in RPMI 1640 medium supplemented with 2 mM glutamine, 10% FBS (all from Euroclone, Milano, Italy) and 110 mM gentamicin (PHT Pharma, Milan, Italy).…”
Section: Cells and Virusmentioning
confidence: 99%
“…Previous studies have revealed that the activity of therapeutic Abs can be enhanced by creating multivalent constructs such as ILs [33, 35]. Combination of multiple monoclonal antibodies has shown synergistic therapeutic effects in B cells leukemia [40, 41]. Therefore, the dual mAbs on the same ILs may potentially enhance the cross-linking induced apoptosis of CLL B cells.…”
Section: Resultsmentioning
confidence: 99%
“…Yeh et al found increased transferrin binding in peripheral blood mononuclear cells from patients with leukemia, lymphoma and myeloma [29]. In B-cell chronic lymphocytic leukemia, CD71 expression is heterogenous, with some cases showing high expression [30][31][32]. Both B and T lineage non-Hodgkin's lymphomas have been reported to express CD71, with the expression level correlating with the lymphoma grading, though not with patient survival [18,33].…”
Section: Discussionmentioning
confidence: 99%